'If You Find Out Who Her Father is I Would Be Interested to Know' The Kwermin in an Eastern Min Context. Issue 2 (14th July 2013) - Eggertsson, Sveinn
Abstract In this paper the peripheral position of the Kwermin in the Min regional context is discussed through a focus on two gift‐presentations, those of bridewealth and those presented to fully initiated men at the end of their initiatory process. The items of the traditional bridewealth gifts are discussed as well as the debate that emerged, after the discontinuation of this traditional presentation, whether Kwermin should take up the large bridewealth payments introduced from the highland Bimin or go back to an earlier custom of sister‐exchange (abu) between clans without great emphasis on bridewealth. However, it is suggested that the present day monetary claims, without their actual payment, may eventually serve to strengthen the previous practice of abu. The gifts presented following full initiation are referred to as Afek's pubic hair and it is shown how these presentations can be understood as being Afek, or essential aspects of this highland's originating ancestor, creating novices as true men who are then presented to Afek in a way similar to the way wives are presented to husbands. It is suggested that such presentation of man to ancestress partly explains patriarchal Kwermin men's reluctance to fully accept highland ideology, preferring to maintain their allegiance with the cultural hero of the lower mountains and the lowlands, Webnok.